2021
DOI: 10.5187/jast.2021.e7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of formic acid and lactic acid bacteria inoculant on main summer crop silages in Korea

Abstract: To improve the fermentation quality of silage and reduce the nutrients loss of raw materials during the ensiling process, silage additives are widely used. The effect of additives on silage is also affected by the species of crop. Therefore, this study was designed to explore the effects of formic acid (FA) and lactic acid bacterial inoculant on the quality of main summer crop silage. The experiment was consisted on split-plot design with three replications. The experiment used the main summer forage crops of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…[ 4 ] also reported that total dry biomass in proso millet averaged 6.43 t/ha. Data of NDF and CP concentration of these forage crops is previously reported [ 8 ]. NDF was highest in sorghum-sudangrass hybrid, intermediate in proso millet, and lowest in corn.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 4 ] also reported that total dry biomass in proso millet averaged 6.43 t/ha. Data of NDF and CP concentration of these forage crops is previously reported [ 8 ]. NDF was highest in sorghum-sudangrass hybrid, intermediate in proso millet, and lowest in corn.…”
Section: Resultsmentioning
confidence: 99%
“…Silage pH was determined in the filtrate with a pH meter (AB 150, Fisher Scientific International, Inc., Pittsburgh, PA, US). A 1.5 mL portion of the filtrate was used for analysis of the organic acid concentration using high performance liquid chromatography (HPLC, Agilent Technologies, Santa Clara, CA, US) equipped with a refractive index detector [8]. Ammonia nitrogen (NH3-N) was analyzed via the method described by Broderick and Kang [14].…”
Section: Analytical Analysesmentioning
confidence: 99%
See 3 more Smart Citations